Adapting the Planetary Health Diet Index for children and adolescents - Carolina Venegas Hargous; Liliana Orellana; Claudia Strugnell; Camila Corvalan; Steven Allender; Colin Bell (BMC, 2023)
Abstract Background Tools for measuring adherence to sustainable healthy diets among children and adolescents are lacking. Objective To advance methods for measuring adherence to sustainable healthy diets among children and adolescents by adapting an existing index, compare scores obtained using the original and adapted versions of the index in a sample of Chilean children, and describe the adapted index association with diet characteristics. Methods The Planetary Health Diet Index (PHDI) was adapted to better reflect children's and adolescents' nutritional requirements. The adapted index (PHDI-C) comprises 16 components with a maximum score of 150 points. PHDI-C was piloted among a sample of 958 Chilean children (3-6 years) using dietary data collected in 2016 through single 24-h recalls. A decision tree and food disaggregation methodology were developed to guide the calculation of scores. Scores obtained using the original and adapted versions of the index were compared. Linear regression models adjusted by child's gender and age were fitted to explore associations between total PHDI-C score, dietary recall characteristics and nutritional composition of children's diets. Results PHDI accounted for 75.7% of children's total caloric intake, whereas PHDI-C accounted for 99.6%. PHDI & PHCI-C scores were low among this sample of children; however, mean total score was lower when using PHDI compared to PHDI-C [40.7(12.1) vs 50.1(14.6)]. Children's scores were very low for nuts & peanuts, legumes, dark green vegetables, whole cereals, tubers & potatoes, and added sugars components across both indices, but were higher for dairy products and eggs & white meats components when using the PHDI-C due to adjustments made to ensure nutritional adequacy. Mean total PHDI-C score was significantly lower on weekends and special occasions, and significantly higher when children reported having a special diet (e.g., vegetarian). Total PHDI-C score was negatively associated with total sugars, saturated fats, trans fats, and animal-based protein intake, and positively associated with total protein, plant-based protein, total carbohydrates, and total fibre intake. Conclusions This study provides a replicable method for measuring adherence to sustainable healthy diets among children and adolescents that can be used to monitor trends and measure the effectiveness of actions targeting improving children's diets.